2014
DOI: 10.1155/2014/947513
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Vascular Endothelial Growth Factor in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal devastating neurodegenerative disorder, involving progressive degeneration of motor neurons in spinal cord, brainstem, and motor cortex. Riluzole is the only drug approved in ALS but it only confers a modest improvement in survival. In spite of a high number of clinical trials no other drug has proved effectiveness. Recent studies support that vascular endothelial growth factor (VEGF), originally described as a key angiogenic factor, also plays a key role in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 291 publications
(417 reference statements)
0
45
0
Order By: Relevance
“…A recently published study demonstrated that microRNA‐containing exosomes derived from maternal and umbilical cord serum dramatically promote human umbilical vein endothelial cell proliferation, migration, and tube formation in vitro, highlighting the important role of exosomes in the regulation of angiogenesis during gestation. Exclusively, VEGF has been studied for potential therapeutic efficacy in animal models of ALS and its use in clinical settings has been discussed (reviewed). Nevertheless, CBP containing high levels of IL‐8 and VEGF might be a beneficial treatment for repair of the damaged blood–brain barrier and/or blood–spinal cord barrier in patients with ALS, AD, Parkinson's disease and multiple sclerosis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published study demonstrated that microRNA‐containing exosomes derived from maternal and umbilical cord serum dramatically promote human umbilical vein endothelial cell proliferation, migration, and tube formation in vitro, highlighting the important role of exosomes in the regulation of angiogenesis during gestation. Exclusively, VEGF has been studied for potential therapeutic efficacy in animal models of ALS and its use in clinical settings has been discussed (reviewed). Nevertheless, CBP containing high levels of IL‐8 and VEGF might be a beneficial treatment for repair of the damaged blood–brain barrier and/or blood–spinal cord barrier in patients with ALS, AD, Parkinson's disease and multiple sclerosis …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the elevated level of VEGF is a result of the high concentration of IL-8, which promotes increased expression of VEGF by endothelial cells. 35,36 A recently published study 37 Exclusively, VEGF has been studied for potential therapeutic efficacy in animal models of ALS 38,39 and its use in clinical settings has been discussed (reviewed 40 ). Nevertheless, CBP containing high levels of EHRHART ET AL.…”
Section: Cord Blood Plasma Growth Factor Profilementioning
confidence: 99%
“…Hence, it is likely that an interaction also occurs between profilin1 and the unmodified mDia . Profilin1 also interacts with vascular endothelial growth factor (VEGF), a small protein and a known neurotropic factor involved in angiogenesis, which also was implicated recently in cell signaling and tumorigenesis [23]. Specifically, VEGF-A binding to VEGF receptor 2 (VEGFR2) triggers phosphorylation of profilin1 Y129, increasing profilin1’s affinity for actin and thereby enhancing actin polymerization at the edge of the cell - the filopodium effect (Figure 1A).…”
Section: Profilin1 Protein-protein Interactionsmentioning
confidence: 98%
“…In one particular study, VEGF-A had promising results, with neuroprotection of motor neurons significantly improving neuronal survival in animal models [52]. However, as previously mentioned, the issues with VEGF-A's safety profile remain.…”
Section: Neuroprotective Role Of Vegf-b In Amyotrophic Lateral Sclmentioning
confidence: 99%